2015
DOI: 10.1021/acsnano.5b03199
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Detection of Active Edge Sites in Single-Layer MoS2 Catalysts

Abstract: MoS2 nanoparticles are proven catalysts for processes such as hydrodesulfurization and hydrogen evolution, but unravelling their atomic-scale structure under catalytic working conditions has remained significantly challenging. Ambient pressure X-ray Photoelectron Spectroscopy (AP-XPS) allows us to follow in situ the formation of the catalytically relevant MoS2 edge sites in their active state. The XPS fingerprint is described by independent contributions to the Mo 3d core level spectrum whose relative intensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
159
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 42 publications
26
159
3
Order By: Relevance
“…This feature seems to be in agreement with earlier calculations [12,13,26] and possibly with the scanningtunneling-microscope images of MoS 2 triangles exhibiting a period of two along the Mo edges [12,15,27]. The resulting structure and the corresponding S 2 −S 2 distances are shown in Fig.…”
Section: Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…This feature seems to be in agreement with earlier calculations [12,13,26] and possibly with the scanningtunneling-microscope images of MoS 2 triangles exhibiting a period of two along the Mo edges [12,15,27]. The resulting structure and the corresponding S 2 −S 2 distances are shown in Fig.…”
Section: Modelssupporting
confidence: 91%
“…It is understood that the edges of the MoS 2 nanoclusters are catalytically active [11][12][13] and that this is due to the existence of metallic states present at certain edge configurations [14][15][16][17][18]. It has recently been shown that these states can lead to the formation of plasmons, i.e., quantized oscillations of electron gas plasma, along the edges of infinite MoS 2 nanoribbons [19].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the absence of reactivity of the pristine s‐ MoS 2 is attributed to the fully sulfided nature of both basal plane sites and the edges, which leaves no affinity for direct chemical bonding to the thiophenic S group of DBDBT nor for activation of the debromination step to allow for bonding to C. The Mo‐edge, exposed both in the pristine triangular NP‐MoS 2 and SL‐MoS 2 , are terminated by a full (100%) sulfur coverage as determined from previous atom‐resolved STM and theory studies (see Figure 1e). The terminal edge sulfurs in s ‐MoS 2 form stable S 2 dimers by combination of the S from the upper and lower layer,37,38 respectively, which may further explain the absent reactivity here. The S edges are present in the hexagonal SL‐MoS 2 structures, and are likewise terminated by a full (100%) sulfur coverage as shown in Figure 1e 38–40…”
Section: Resultsmentioning
confidence: 75%
“…Figure 17 shows STM images for RuS 2 and MoS 2 on a Au(111) substrate. 75,76 The ionic character of these compounds is smaller than in an oxide and they do have catalytic properties on their own. 76 …”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%